The implications of expectancy-value theory of motivation in language education - Wang, Qi; Xue, Mengchen (Frontiers in Psychology, 2022)
Abstract The successful performance of learners in any field of study, including a second/foreign language, is deemed as a pivotal concern in the educational system. Furthermore, the various learner variables, in particular, motivation should be taken into consideration, as a high level of motivation can yield many positive outcomes. Literature introduces the expectancy-value theory (EVT) as a recent approach to motivation, which has caught the attention of researchers. EVT as a basic and integrated paradigm helps the researchers and teachers to understand learners’ motivations and behaviors, and it has proved to be very helpful in understanding cognitive processes used by the learners, as well as their achievement. Based on this theory, successful performance, including the successful completion of the task and future aspirations, is mainly impacted by perceived expectancies regarding the outcome and value of tasks or domains. EVT can be viewed as a lens through which the aspects of motivation can be seen. This would pave the way for learners’ engagement and their achievement. EVT attaches great importance to learners’ reasonable expectations regarding the accomplishment of a goal. It also emphasizes figuring out the value of achieving the learning goal, which would enhance the motivation for L2 learning. The current review is aimed at examining how the expectancy-value motivational model impacts academic motivation, engagement and participation in educational tasks, and learners’ academic performance.